Ethical Journalism: News Coverage of Terrorism - Ayten Gorgun Smith; Banu Baybars Hawks (Journal of Management Practices, Humanities and Social Sciences, 2019)
This article aims to examine how news media cover terrorism, and how public opinion has been influenced by the media coverage, with examples from different parts of the world. Media coverage of attacks, attackers or the activities of terror organisations informs the public, but it also serves as a major channel to spread the terror, and at the same time, these news get the attention of possible recruits to terror organisations. Thus, media coverage can directly and indirectly assist terrorist organisations to reach their goals. This paper will try to reveal whether the media, intentionally or unintentionally, reflects exaggerated accounts of violent terrorist acts or not. In this regard, ethical standards in the coverage of terrorism will be discussed. Content analysis of the recent attacks in the mosques of New Zealand and explosions in the churches and various places in Sri Lanka from Al Jazeera, the BBC, CNN, and The New Zealand Herald's (for New Zealand), and The Daily Mirror (for Sri Lanka) website articles, are undertaken by keyword searching. The findings highlight that all of the studies' mediums avoided giving their own commentary or opinion, Al Jazeera framed the news mostly from the view of Muslim groups and the CNN and the BBC avoided to use “terrorist” phase. Besides, in terms of the ethics of journalism, both indicating the attacker's identity in the news and approaching the events with moderate words due to the identity of the attacker are problematic.